Ectopic bone formation by gel-derived bioactive glass-poly-L-lactide-co-glycolide composites in a rabbit muscle model. (17th January 2017) - Filipowska, Joanna; Cholewa-Kowalska, Katarzyna; Wieczorek, Jarosław; Semik, Danuta; Dąbrowski, Zbigniew; Łączka, Maria; Osyczka, Anna M
Abstract: In this study we aimed to assess the in vivo osteoinductive properties of two composite scaffolds made of PLGA (poly-L-lactide-co-glycolide) and two types of gel-derived bioactive glasses, namely a high silica S2 bioactive glass (S2-PLGA composites) or high lime A2 bioactive glass (A2-PLGA composites). To achieve that, the potential of the composites to induce ectopic bone formation in a rabbit muscle has been examined along with the control PLGA scaffold. Cylinder-like scaffolds of 7 × 3 mm (width × height) were implanted into pouches created in the latissimus dorsi muscle of 18 New Zealand rabbits. The tissue sections were obtained at 6, 12 or 24 weeks post-surgery (six rabbits per each time point) and stained with hematoxylin-eosin. The process of wound healing, the formation of collagen-rich connective tissue and its transition to cartilage were examined by Sirius red and Alcian blue histological stainings. We also performed immunohistochemical verification of the presence of osteoblast- and osteoclast- like cells in the vicinity of the scaffolds. A typical foreign body reaction and wound healing process was observed for all implanted scaffolds. Osteoblast- and osteoclast-like cells were observed in the vicinity of the scaffolds as determined by the immunohistochemical staining for Osteocalcin, BMP-2 and Cathepsin K. Compared to plain PLGA scaffolds, numerous osteoblast-like cells were observed 12 weeks post implantation near the composites and the scaffolds gradually degraded as bone formation proceeded. S2-PLGA and A2-PLGA composites display osteoinductive properties in vivo . Furthermore, they are more effective at inducing ectopic bone formation in a rabbit muscle compared to plain PLGA. Thus these SBG-PLGA composite scaffolds have potential for clinical applications in dental and/or orthopedic-bone tissue engineering.